Supervision of The Prevention of Narcotics Distribution In Class IIa Bengkalis Penitentiary - Hasan, Muhamad; Simanjuntak, Harapan Tua Ricky Fredy; As'ari, Hasim (Department of Public Administration, 2023)
This study aims to analyze and explain as well as identify obstacles in the supervision of prevention of narcotics distribution in Bengkalis Class IIA Penitentiary. In this study, an empirical juridical approach is applied which remains based on normative premises where the operational definition is taken from laws and regulations to then look at the reality on the ground. Primary data were obtained from observations and interviews with leaders, officers and prisoners of Class IIA Bengkalis Penitentiary. Secondary data was obtained from documentation owned by the Bengkalis Class IIA Penitentiary and from literature studies.The conclusion of the study is that supervision in preventing drug trafficking in the Bengkalis Class IIA Penitentiary has followed the Standard Operational Procedure (SOP) in the Decree of the Director General of Corrections of the Ministry of Law and Human Rights of the Republic of Indonesia Number: PAS-416.PK.01.04.01. 2015 and Decree of the Director General of Corrections of the Ministry of Law and Human Rights of the Republic of Indonesia Number: PAS-36.OT.02.02 of 2020. The results of the evaluation show that there are several obstacles in supervision, such as: Executing Officers do not yet have the ability to identify types of narcotics and do not have standard expertise as self-reliance coaches; There is no x-ray sensor device for inspection of objects that are prohibited from entering and objects attached to the body; Minimal training facilities and infrastructure.Â